2012
DOI: 10.1111/j.1365-2621.2012.03214.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, in vitro starch digestibility and amino acid analysis of a underexplored kidney bean (Phaseolus vulgaris. L.) grown in Chongqing, China

Abstract: Summary Chemical composition, mineral analysis, in vitro starch digestibility, and amino acid analysis of a kidney bean (Phaseolus vulgaris. L.), grown in Chongqing, China, were carried out in 2011. The results showed that the bean flour contained low reducing sugar (0.79%) and fat (2.72%), but high protein (24.8%) and starch (44.84%). Mineral analysis indicated high Mg and Ca contents with low Na/K ratio (0.04). The proportions of rapidly digestible starch (RDS), slowly digestible starch (SDS) and resistant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The maceration of the sample appears to have minimized any glycemic difference, which may have existed in the sample, whereas the chewing preparative step appears to retain the glycemic differences inherent in the product. Many researchers have studied the effect of different legume flours on starch digestibility in a range of food products . Their results are similar to our observations from the chewed samples in that spaghetti made with semolina generally showed a significantly higher enzymatic hydrolysis rate compared to samples made with legume flours.…”
Section: Resultssupporting
confidence: 87%
“…The maceration of the sample appears to have minimized any glycemic difference, which may have existed in the sample, whereas the chewing preparative step appears to retain the glycemic differences inherent in the product. Many researchers have studied the effect of different legume flours on starch digestibility in a range of food products . Their results are similar to our observations from the chewed samples in that spaghetti made with semolina generally showed a significantly higher enzymatic hydrolysis rate compared to samples made with legume flours.…”
Section: Resultssupporting
confidence: 87%
“…Glycine, malic acid, and palmitic acid were higher in the CB. Relatively fewer reports are available in literature regarding the variations of individual amino acids in different beans (Mundi and Aluko ; Liu and others ). Amino acids are classified into essential and nonessential groups.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Feregrino-P erez et al ( 2008) and Mart ın-Cabrejas et al (2004) did not find an effect of cooking or autoclaving, respectively, on RS and other authors found that subjecting beans to pre-cooking, cooking or other thermal treatments can increase and sometimes almost double, the RS concentration (Granito et al, 2007;Chung et al, 2010;Liu et al, 2013;Reddy et al, 2013;De Pasquale et al, 2020). Yadav et al (2010b) found no effect of the cooking strategy on RS concentration of beans, but they did not report the RS concentration of the raw material.…”
Section: Rs In Phaseolus and Its Variation Due To The Food Treatmentmentioning
confidence: 91%